Engineering cottonseed for use in human nutrition by tissue-specific reduction of toxic gossypol - Sunilkumar, Ganesan (National Academy of Sciences, 2006)
Global cottonseed production can potentially provide the protein requirements for half a billion people per year; however, it is woefully underutilized because of the presence of toxic gossypol within seed glands. Therefore, elimination of gossypol from cottonseed has been a long-standing goal of geneticists. Attempts were made to meet this objective by developing so-called “glandless cotton” in the 1950s by conventional breeding techniques; however, the glandless varieties were commercially unviable because of the increased susceptibility of the plant to insect pests due to the systemic absence of glands that contain gossypol and other protective terpenoids. Thus, the promise of cottonseed in contributing to the food requirements of the burgeoning world population remained unfulfilled. We have successfully used RNAi to disrupt gossypol biosynthesis in cottonseed tissue by interfering with the expression of the δ-cadinene synthase gene during seed development. We demonstrate that it is possible to significantly reduce cottonseed-gossypol levels in a stable and heritable manner. Results from enzyme activity and molecular analyses on developing transgenic embryos were consistent with the observed phenotype in the mature seeds. Most relevant, the levels of gossypol and related terpenoids in the foliage and floral parts were not diminished, and thus their potential function in plant defense against insects and diseases remained untouched. These results illustrate that a targeted genetic modification, applied to an underutilized agricultural byproduct, provides a mechanism to open up a new source of nutrition for hundreds of millions of people.